Evaluation of post-earthquake fractures according to anatomical body parts: A retrospective study - Muhammed Furkan Arpaci; Ferhat Tas; Gokce Bagci Uzun; Mehmet Akcicek; Feyza Inceoglu; Mine Argali Deniz; Emre Demirel; Hidir Pekmez (Medicine Science)
Bone fractures that occur in earthquakes threaten human life. The study aims to localize the fractures in earthquake victims according to anatomical regions in the earthquake centered in Kahramanmaraş 2023. The study included 137 patients aged between 1-90 years diagnosed with fractures by an orthopedic physician. Radiographs were taken of patients admitted to the emergency department after the earthquake. The fractures diagnosed patients were evaluated and classified in anatomical regions and fracture type. The fractures were observed in females with high rates of fragmented (49.6%) and s ingle fractures (75.9%). The fractures also occurred on the right side (58.4%), in the upper extremities (37.2%) and long bones (38.7%). In the specific anatomic region evaluation of fractures; high rates were observed in manus (19%), antebrachi (15.3%), crus (13.9%) and pes fractures (12.4%). In the region of the most common fragmentary fracture type (48.9%); omos (3%), brachium (1%), thorax (15%), viscerocranium (7%) and neurocranium (3%), in oblique fractures (25.5%); pes (26%), in transverse fractures (20.4%); antebrachi (21%), manus (32%) and vertebral column (4%), in spiral fractures; pelvis (14%), femur (14%) and crus (57%) region. We determined that fractures frequently occur on the right-side extremities and, besides sequentially high rates at manus, antebrachii, crus, and pes. We recommend providing information about the protection of these anatomical parts in the training given to people during the earthquake closure and post-earthquake panic times to reduce earthquake-related fractures. [Med-Science 2024; 13(4.000): 809-14]